Kasus Multiproduk dan Multivariabel Toko Kain Avtex Menggunakan Diagram Kontrol Short-Run - Vega Rochwani Putri; Siti Sunendiari (UNISBA Press, 2021)
Abstract. A method for quality control that can provide an overview of the ongoing process by taking samples for analysis using statistical techniques so that variability in the process can be reduced is called Statistica Process Control (SPC), which has the aim of quickly detecting the presence of the cause of cases of shifting a process. so that improvements can be made to the process before too many processes are not in accordance with running standards. The design and implementation of a production must be observed sequentially from the state of the mass product for this to be effective. In short production run (Short Production Run) usually do not have sufficient data sufficient to carry out SPC using classical diagrams due to different products. To find out whether the process is controlled or not, it is presented in the Short-Run Control Diagram for X and R. In making a short-run control diagram R and X for multi-products that are measured are one item. Then determine the Upper Control Limit (UCL) and Lower Control Limit (LCL). Short-Run R and X Kontrol control diagrams for multiproduct and multivariable are discussed in this thesis. The data used are pieces of cordura and shabet fabrics at the AVTEX Fabric Store. Abstrak. Metode untuk mengendalikan kualitas yang dapat memberikan gambaran tentang proses yang sedang berjalan dengan mengambil sampel untuk dianalisa dengan menggunakan tehnik statistik sehingga variabilitas dalam proses dapat dikurangi disebut Statistica Proses Control (SPC), yang memiliki tujuan untuk mendeteksi secara cepat kehadiran penyebab kasus dari pergeseran suatu proses sehingga dapat dilakukan perbaikan terhadap proses tersebut sebelum terlalu banyak proses yang tidak sesuai dengan standar berjalan. Rancang dan implementasikan suatu produksi harus diamati berurutan dari kondisi produk massal agar hal ini dapat efektif. Pada produksi jangka pendek (ShortProduction Run) biasanya tidak memiliki data yang cukup memadai untuk melaksanakan SPC dengan menggunakan diagram klasik karena produk yang berbeda. Untuk mengetahui proses terkendali atau tidak maka disajikan pada Diagram KontrolShort-Run untuk X ̅ dan R. Dalam membuat diagram kontrol short-run R dan X ̅ untuk multiproduk yang diukur adalah satu item. Kemudian ditentukan Upper Control Limit ( UCL) dan Lower Control Limit ( LCL). Diagram KontrolShort-Run R dan X ̅ untuk multiproduk dan multivariabel dibahas dalam skripsi ini. Data yang digunakan yaitu potongan kain cordura dan shabet di Toko Kain AVTEX.